BANK SYARIAH INDONESIA (BSI) STRATEGY IN DEALING WITH NATIONAL COMPETITION IN FINANCIAL INSTITUTIONS - Muhammad Reza Iriawan; Tuti Anggraini (Jurnal Ekonomi, 2023)
In this study, it examines in depth related to the merger carried out by BSI bank and examines before and after the merger of the bank and examines sharia regarding mergers. The method used is descriptive qualitative, using secondary data to obtain documents and the results of previous research. The analysis technique in this study was carried out descriptively by summarizing the research data, then displaying the data and drawing conclusions according to the research results. The results of this study are that the merger strategy carried out by BSI bank is by combining 3 large Islamic banks in Indonesia. Then carry out international cooperation with Dubai to support the quality and performance of the BSI bank. The impact after this merger has had a good effect, which is based on the data it can be seen that the total assets, the amount of financing, the amount of third party funds and the amount of profit increased when the merger was carried out. As for sharia studies, it has allowed the merger to take place while having a positive impact and not contradicting sharia law.